North Italy: Welcome to the Tropics! - Federica Veronese; Francesca Graziola; Pamela Farinelli; Elisa Zavattaro; Vanessa Tarantino; Elia Esposto; Paola Savoia (Infectious Disease Reports, 2021)
We describe a case of cutaneous Larva Migrans in an 8-year-old Caucasian girl. The lesion appeared ten days after a bath in the river in a valley in the north-east of Piedmont. The patient was successfully treated with Albendazole 400 mg daily for 5 days. Autochthonous cases are rare, particularly in northern Italy. Probably the high temperatures and the high degree of humidity favored by the climate changes to which Europe is subjected are favorable to the development of larvae. The diagnosis of cutaneous Larva Migrans should, therefore, be considered also in individuals who have not traveled in geographic areas at risk for the climate.